PARTISIPASI MASYARAKAT DALAM PROGRAM PELATIHAN NUGGET SAYUR - Aulia, Lintang Zulfa; Nur Apriliani, Zahra; Fauzan, Fauzan; Maharani Anjasani, Putri; Novitasari, Nastiti (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The title of this activity is about community participation in a vegetable nugget making training program in Sukajaya Village aimed at housewives, especially mothers who have toddlers. This activity was held based on problems in the field that there are still children who experience malnutrition caused by food that does not contain good nutrition. This activity consists of several stages of community participation consisting of the planning or socialization stage, the implementation stage, the evaluation stage, and the benefit-taking stage. This activity also received a positive response from the surrounding community as evidenced by the form of community attendance who participated in the activity. With this activity, it is hoped that mothers who have children can pay more attention to healthy food for children and become a new alternative regarding food innovations that have good nutrition.